Grafologi pada Penulisan Surat Lamaran Pekerjaan di PT Holli Karya Sakti Grobogan - Imam Dzulfikar (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2020)
This paper aims to describe more detailed information about the relationship ofhandwriting and the human brain is very close to handwriting can be used as one tool tostudy the human character. The study used a documentation in the form of photocopyof several application letter of job. The data already obtained in the previous stage is thenanalyzed. The process of this analysis is done by comparing handwriting with referencegraphology books. The data that have been analyzed further presented the results in thereport in the form of a complete description descriptively related to graphology analysisin the writing of job application letter in PT. Holi Karya Sakti Grobogan district. Theresults show that conclusions as follows (1) Comparative handwriting test with referencegraphology book allows users to know the characters they have. (2) This comparison testmakes it easy for users to get information related to human characters from handwriting,as well as to provide some graphological insight.